Radfahren in Wien. - Lehmann, Jana Sophie (My University, 2015)
Auf Basis der Theorie des geplanten Verhaltens und der Proportion Dominance werden Aspekte untersucht und diskutiert, die im Zusammenhang mit der wahrgenommenen Sicherheit des Radfahrens und der Verhaltensabsicht stehen, das Rad im Wiener Stadtverkehr als bevorzugtes Verkehrsmittel zu wählen. Um diese Zusammenhange zu prüfen, wurden mittels eines Online-Fragebogens (N = 614) Personen befragt. Die Einflussvariablen wahrgenommene Sicherheit, wahrgenommene Verhaltenskontrolle, Nettoeinkommen, Geschlecht und Arbeitsstatus konnten jeweils die Intention Rad zu fahren vorhersagen. Wohingegen die soziale Norm beim Radfahren, Alter, Beziehungsstatus, Bildungsabschluss, Wegstrecke und Wegezweck keine Vorhersage für die Verhaltensabsicht das Rad im Wiener Stadtverkehr als bevorzugtes Verkehrsmittel zu nutzen, darstellten. Außerdem schienen Fahrradfahrer, Personen des Öffentlichen Nahverkehrs (ÖPNV) und des Motorisierten Individualverkehrs (MIV) die Sicherheit des Radfahrens unterschiedlich wahrzunehmen. Der Effekt der Dominanz der Proportionen konnte in diesem Zusammenhang nicht bestätigt werden. Mittels eines Strukturgleichungsmodells wurde die Theorie des geplanten Verhaltens geprüft.

As declared by current coalition - between Green Party and Labor Party - the city council of Vienna aims to change the dominant way of urban transport: instead of motorized private transport, the city council wants to promote environmentally friendly alternatives such as cycling. On the basis of the Theory of Planned Behavior and the Proportion Dominance, this paper examines aspects that are associated with perceived safety of cycling and the motivation to ride a bike. In order to analyze the relationship between perceptions of safety and the motivation to ride a bike, N = 614 persons were interviewed online. The results showed that perceived safety, perceived behavior control, net income, gender as well as work status may trigger the motivation to ride a bike. However, variables such as social norm, age, relationship status, educational achievement, route distance and destination did not explain whether people ride their bikes on a daily basis. Moreover, cyclists, people using public transport and people using private motorized transport seemed to perceive safety of cycling differently. The effect of the proportion s dominance cannot be supported in this context. The theory of planned behavior was tested by structural equation modeling. The models showed an acceptable fit to the data. Parts of the socio-demographic data turned out to be predictors of manifest variables in the model. Further studies should expand these models in order to investigate the complexity that lies behind the motivation to use bikes as a primary means of commuting.
Cycling in Vienna.
Keywords: Individualverkehr; Fahrradverkehr; Sozialpsychologie; Verkehrsverhalten; Verkehrsmittelwahl; Stadtverkehr; Verkehrssicherheit; Wahrnehmung; Befragung; Bevölkerungsstruktur; Soziodemographie; Radfahrer; Verkehrsteilnehmer; Empirische Untersuchung